Bosnia and Herzegovina : Staff Report for the First Review Under the Stand-By Arrangement. (IMF Staff Country Reports; Country Report, 2010)
The staff report for Bosnia and Herzegovina's (BiH) first review under the Stand-By Arrangement is presented. The precipitous drop in demand for BiH's exports and the drying up of foreign direct investment triggered a sharp decline in private investment. Tightening credit conditions and the ensuing uncertainty put a further squeeze on spending on capital goods and consumer durables. Private consumption of nondurables softened but to a lesser extent, on the back of moderate growth in wages and social benefits.